Public disclosure for pollution abatement: African decision-makers in a PROPER public good experiment - Wisdom Akpalu; Babatunde Abidoye; Edwin Muchapondwa; Witness Simbanegavi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
A linear public good experiment has been employed to investigate strategic behaviour in pollution abatement among African climate decision-makers. The experiment consisted of three groups of which Group 1 did not receive any treatments, and Groups 2 and 3 received one and two treatments, respectively. We found that the untreated group (baseline) polluted more than the two treated groups, while there was no statistically significant difference between the pollution abatement of the two treated groups. The results suggest that public disclosure potentially drives pollution abatement and that its eventual withdrawal does not obliterate abatement behavior. We also find that pollution levels differ significantly between males and females. Furthermore, we learned that individuals who thought it was unfair for Africa to reduce emissions polluted more.
Keywords: C91; C92; Q53; Q54; 330; public good experiment; pollution control; public disclosure; Africa